Fig. 19 in Cambrian microfossils from glacial erratics of King George Island, Antarctica ... - Wrona, Ryszard (Zenodo, 2004)
Fig. 19. Representatives of Hadimopanella staurata sp. nov. sclerites showing variability in shape and ornamentation. A. ZPAL V.VI/24S24. B. ZPAL V.VI/24S26. C. ZPAL V.VI/24S33. D. ZPAL V.VI/19S9. E. ZPAL V.VI/24S33. F. ZPAL V.VI/24S30, in oblique lateral (F1) and upper (F2) views. G. ZPAL V.VI/24S3, holotype, in oblique lateral (G1) and upper (G2) views. H. ZPAL V.VI/35S24, in oblique lateral (H1) and upper (H2) views. I. ZPAL V.VI/14S9, in oblique lateral (I1) and upper (I2) views. J. ZPAL V.VI/17S8, in oblique lateral (J1) and upper (J2) views. ... : Published as part of Wrona, Ryszard, 2004, Cambrian microfossils from glacial erratics of King George Island, Antarctica, pp. 13-56 in Acta Palaeontologica Polonica 49 (1) on page 43, DOI: 10.5281/zenodo.13285795 ...